ANALISIS INVESTASI EKONOMI DI INDONESIA PASCA PENERAPAN OMNIBUS LAW PADA ERA KEPEMIMPINAN JOKOWI PADA TAHUN 2020-2023 - Icha Oktaviani; Rani Ligar Fitriani (PERFORMANCE: Jurnal Bisnis & Akuntansi, 2026)
This research examines the impact of the Omnibus Law on job creation in Indonesia during President Joko Widodo's administration. Enacted in 2020, the Omnibus Law was intended to simplify regulations, improve the investment climate, and encourage economic growth. The findings show that although the policy has contributed to increased investment and business opportunities, its effect on reducing unemployment and creating jobs has not been fully optimal. This is because a significant portion of incoming investment remains concentrated in capital-intensive sectors with limited labor absorption. In addition, the policy has raised concerns regarding the weakening of worker protections, particularly in relation to job security and labor welfare. Therefore, the effectiveness of the Omnibus Law should not only be measured by higher investment and economic growth, but also by the quality of jobs created and the protection of workers' rights. Continuous evaluation is necessary to ensure that the policy supports inclusive, fair, and sustainable economic development in Indonesia.